Can pensions save lives? Evidence from the introduction of old-age assistance in the UK - Philipp Jäger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
I study the impact of old-age assistance on mortality using the introduction of public pensions in the UK in 1909 as a quasi-natural experiment. Exploiting the newly created pension eligibility age through a difference-in-difference as well as an event-time design, I show that elderly mortality in England and Wales declined after the pension was introduced. The estimated mortality decline is economically relevant, more pronounced in counties with a higher share of pensioners and is driven by fewer deaths from infectious as well as non-infectious diseases. An analysis of full-count individual-level census data points to a reduction in residential crowding and retirement, especially from occupations associated with high mortality rates, as likely channels. – – In diesem Beitrag werden die Auswirkungen von öffentlichen Alterssicherungssystemen auf die Sterblichkeit untersucht. Dazu nutze ich die Einführung öffentlichen Renten im Vereinigten Königreich im Jahr 1909 als quasi-natürliches Experiment. Unter Ausnutzung des neu geschaffenen Renteneintrittsalters durch ein differences-in-differences sowie ein Event-time-Design, zeige ich, dass die Sterblichkeit älterer Menschen in England und Wales nach der Einführung der Rente zurückgegangen ist. Der geschätzte Rückgang der Sterblichkeit ist ökonomisch signifikant, in Bezirken mit einem höheren Anteil an Rentnern stärker ausgeprägt und wird durch weniger Todesfälle durch infektiöse und nicht-infektiöse Krankheiten verursacht. Eine Analyse von individuellen Volkszählungsdaten, welche die gesamte Bevölkerung umfassen, deutet auf zwei Wirkungskanäle hin. Durch die Rente: 1) konsumieren Ältere mehr Wohnraum, 2) gehen Ältere vermehrt in den Ruhestand (insbesondere in Berufen, die mit hohen Sterblichkeitsraten verbunden sind).
Keywords: H55; I12; J14; J26; 330; Old-age assistance; mortality; retirement